2011
DOI: 10.1103/physrevd.83.025008
|View full text |Cite
|
Sign up to set email alerts
|

Superconformal symmetry, NMSSM, and inflation

Abstract: We identify a particularly simple class of supergravity models describing superconformal coupling of matter to supergravity. In these models, which we call the canonical superconformal supergravity (CSS) models, the kinetic terms in the Jordan frame are canonical, and the scalar potential is the same as in the global theory. The pure supergravity part of the total action has a local Poincaré supersymmetry, whereas the chiral and vector multiplets coupled to supergravity have a larger local superconformal symme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
433
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(446 citation statements)
references
References 95 publications
13
433
0
Order By: Relevance
“…This time only the unprotected field φ−φ receives a mass of order H. Examples of supersymmetric inflation models with these structures can be found in [221,222,239,241,522,523]. Further work on inflation in supergravity includes [480,[524][525][526][527][528][529]. A fundamental limitation of simply assuming a shift symmetry in the low-energy supergravity is that couplings to Planck-mass degrees of freedom 10 A criticism of D-term inflation based on consistency conditions in supergravity can be found in [518].…”
Section: The Eta Problem In Supergravitymentioning
confidence: 99%
“…This time only the unprotected field φ−φ receives a mass of order H. Examples of supersymmetric inflation models with these structures can be found in [221,222,239,241,522,523]. Further work on inflation in supergravity includes [480,[524][525][526][527][528][529]. A fundamental limitation of simply assuming a shift symmetry in the low-energy supergravity is that couplings to Planck-mass degrees of freedom 10 A criticism of D-term inflation based on consistency conditions in supergravity can be found in [518].…”
Section: The Eta Problem In Supergravitymentioning
confidence: 99%
“…It has been shown that HI in the framework of supergravity (SUGRA) can be implemented by imposing [17][18][19][20][21][22][23][24][25][26][27][28][29][30] a convenient shift symmetry on the Kähler potential or invoking [31][32][33][34][35][36][37][38][39][40][41] a logarithmic Kähler potential with a real subdominant kinetic part and a dominant holomorphic (and anti-holomorphic) part, which plays the role of a non-minimal coupling to the Ricci scalar curvature [42][43][44][45][46][47]. Inspired by these efforts, we present here a 'hybrid' scenario, where a conjugate pair of Higgs superfields is involved in the logarithmic part of the Kähler potential K, which respects a shift symmetry with a tiny violation -cf.…”
Section: Jhep11(2015)114mentioning
confidence: 99%
“…We begin with the encouraging observation that by a simple change of the field variable φ 2 = ΦΦ = 6 tanh 2 (δσ) (with κ 2 = 2) our self-dual models (4.4) are transformed into SU(1, 1)/U(1) Kähler sigma models, 6 with gauge fixed U(1) symmetry Φ =Φ = φ and minimally coupled to Einstein gravity. Indeed such an embedding into N = 1 supergravity with one chiral matter supermultiplet is quite natural and expected due to its well known role in the construction of both quintessence [15-17, 19, 20] and inflationary models [9][10][11][12][13]34]. The new feature, however, consists in a very special relation between the Kähler potential K(Φ,Φ) and the superpotential |Z| = W(φ) = e K 2 |W |,…”
Section: Jhep07(2015)017mentioning
confidence: 99%
“…It is worthwhile to also mention that the inflationary α-attractors [5,6], obtained within the superconformal supergravity approach [12,13], for a special choice of the inflaton potential:…”
Section: Jhep07(2015)017mentioning
confidence: 99%
See 1 more Smart Citation